Using quality indices to evaluate groundwater quality in the semi-arid Guorriguer Plain, Tebessa, northeastern Algeria - Mamour, Djemoui; Halimi, Samia; Bouchema, Nadhir; Khammar, Hichem; Boukhallat, Karima (Journal of Water and Land Development, 2026)
To assess groundwater quality in the semi-arid Guorriguer Plain, Tebessa, northeastern Algeria, two indices were used: the water quality index (WQI) and the groundwater pollution index (GPI). Accordingly, the physical and chemical parameters of 21 groundwater wells were evaluated. Field measurements included pH, temperature, and electrical conductivity, while cation and anion concentrations were analysed in the laboratory. The results show that groundwater resources in the study area are mostly suitable for drinking. A comprehensive assessment of water quality using the WQI and GPI standard indices revealed that approximately 90% of the sampled wells met permissible quality thresholds, with many classified as “excellent” to “good” (WQI < 200). This was confirmed by parallel GPI assessments, which indicated that 90% of samples showed only “minor pollution” to “slight pollution” (GPI < 1.5), suggesting minimal human impact in most areas. However, clear localised deterioration was observed in 10% of the samples located along the southwest-to-northeast axis, where high total dissolved solids (TDS) values (1500–3189 mg∙dm−3) and specific conductivity (>2000 μS∙cm−1) exceeded recommended limits. This was primarily due to the influence of geological formations and, secondarily, to agricultural activity characteristic of this region. This study contributes to a deeper understanding of groundwater quality dynamics in semi-arid regions by integrating several indicators and examining their relationships with natural and human factors to obtain accurate results that can help the responsible authorities improve the management and conservation of these important resources.